Jurisprudential Approach to the Relationship Between Law and Politics in Lithuania - Šlapkauskas, Vytautas; Žalėnienė, Inga; Miežanskienė, Ramunė (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The interaction between law and politics has been an object of discussion in many dimensions, including a legal theoretical perspective. This research is based on the methodology of theoretical work of M. Zamboni who has classified various approaches of contemporary legal theories and introduced typical models of how law relates to politics. The following investigation provides substantive practical observations in accordance with M. Zamboni’s methodological framework, further distinguishing aspects of 1) the relationship of law to politics (static aspect); 2) the relationship between law-making and political order (dynamic aspect); 3) the relationship of legal discipline to political material (epistemological aspect). The investigation concentrates on the national context – explicitly on the case of Lithuania, providing reflective practical indications and substantive outcomes about the relationship between law and politics. We argue that the relationship between law and politics should cover multidimensional aspects, including law-making, structural changes in the performance, interaction in the educational system.
Keywords: interaction between law and politics; law and politics